1957
DOI: 10.2136/sssaj1957.03615995002100040022x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Logging and Slash‐Burning on Soil Structure

Abstract: The effects of logging and slash‐burning on soil structure were investigated on three Reddish Brown Latosol soils in the Coast Range of Western Oregon. Soil samples of the surface 2 inches were collected at 50‐foot intervals along randomly located transects within the clear‐cut areas. Soil samples were also collected in the adjacent uncut timber. The condition of the surface soil was noted at 10‐foot intervals along the transects and was recorded as follows: lightly burned, severely burned, disturbed and unbur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 0 publications
3
32
0
Order By: Relevance
“…Changes in surface soil permeability or porosity may occur as the result of the volatilization of organic compounds that had served to cement soil aggregates (Dyrness and Youngberg 1957). This can result in reduced porosity as impacted aggregates crumble and plug large soil pores (Moehring et al 1966).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in surface soil permeability or porosity may occur as the result of the volatilization of organic compounds that had served to cement soil aggregates (Dyrness and Youngberg 1957). This can result in reduced porosity as impacted aggregates crumble and plug large soil pores (Moehring et al 1966).…”
Section: Discussionmentioning
confidence: 99%
“…High-intensity fires may cause thermal fusion of clay-size particles, increasing silt and sand percentages (Dyrness and Youngberg, 1957;Nishita and Haug, 1972; due to thermal changes in aluminosilicates and iron oxides and hydroxides (Betremieux et al, 1960;Giovannini et al, 1990). Also, post-fire increased erosion rates may select coarser particles or aggregates and favor the loss of fine materials.…”
Section: Changes On Soil Texture Structure and Porositymentioning
confidence: 99%
“…Although canopy openings, increased light levels, and higher soil temperatures resulting from logging could potentially benefit beargrass growth and reproduction (Brockway et al 1983, Maule 1959, Vance et al 2001) most studies have found that logging-related activities result in both short-and long-term reductions in beargrass densities (Shebitz et al 2009a). In a short-term Oregon Cascade Range study examining plant cover and composition (1) prior to clearcut logging, (2) after logging but before broadcast slash burning, and (3) during each of five growing seasons following burning, beargrass disappeared immediately after clearcut logging, remained absent after burning, and reappeared only in trace amounts 4 years later (Dyrness 1965). Clearcutting followed by broadcast burning strongly decreased the abundance of beargrass in a study conducted in high-elevation old-growth Douglas-fir forests of the Oregon and Washington Cascade Ranges.…”
Section: Timber Harvestmentioning
confidence: 99%